Prospects for the use of artificial intelligence in arbitration - Nurakhmetova Г.Г.; Saparbekova Ж.С.; Suleimenova С.Ж. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The article is devoted to the possibilities and problems of application of artificial intelligence (AI) systems in the arbitration of the Republic of Kazakhstan, i.e.: in forensic examination, analytical and organizational work, adjudication, interpretation and analysis of law, as well as control over the adoption and execution of court decisions. In the course of the research the foreign experience of using artificial intelligence systems in the judicial systems of Great Britain, the USA and the Netherlands was analyzed. In addition, three main directions of application of artificial intelligence in judicial proceedings were identified. Based on the application of artificial intelligence in practice, it was determined that the use of the European Charter of Ethics in the legislation of judicial and law enforcement systems leads, as predicted by researchers, to positive and negative consequences of use. In addition, it was determined that the use of artificial intelligence in judicial proceedings can optimize the judicial system, prevent subjective attitudes, corruption and possible miscarriage of justice, and risk is necessary. These include: compliance with the ethical principles of artificial intelligence, the impossibility of ensuring transparency and verifiability of court decisions made by artificial intelligence, their legislative non-approval and non-compliance with the requirements of law, protection of personal information. In conclusion, recommendations are given to prevent the negative impact of the introduction of artificial intelligence in arbitration.